Diskusi Tentang Peran Kearifan Lokal dalam Pemanfaatan Sumber Daya Laut dengan Kelompok Masyarakat Maluku Barat Daya - Posma Sariguna Johnson Kennedy; Suzanna Josephine Tobing; Rutman Lumbantoruan; Emma Tampubolon (Jurnal Pemberdayaan Masyarakat, 2019)
The purpose of this study is to remind that local wisdom must be maintained to maintain natural balance. The activity was conducted to discuss the traditional culture of sasi with a group of people in Southwest Maluku (MBD), through focus group discussions. The MBD community in utilizing natural resources still maintains the sasi tradition, so that the continuity of marine resources can be maintained between generations, even though currently facing various threats due to the influence of globalization and greater economic motivation.